Canister sampling during OASIS Barrow field intensive Spring 2009 - Eric C. Apel (Arctic Data Center)
Several Volatile Organic Compound (VOC) were measured using the whole air gas canisters. One-minute data is reported, although canisters were filled only three times per day, on average. Sample times are reported in Alaska Standard Time (AKST). The measurement sample height for all canisters was at the 18-foot tower location, through the same inlet and silcosteel line as the Trace Organic Gas Analyzer (TOGA) samples for that tower height. Mixing ratios of VOCs in the canisters were determined by later laboratory analysis using Gas Chromatography with Mass Spectrometry (GC-MS) and Gas Chromatography with Flame Ionization Detection (GC-FID). VOC mixing ratios: All mixing ratios are in pptv. Below detection limit -8888 Data not available -9999 Detection limits are < 25 pptv. PI: Eric Apel, apel@ucar.edu. The data are formatted as an Excel document.